2018
DOI: 10.1093/femspd/fty006
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine intervention limits pathogen expansion in vitro

Abstract: Ketamine is one of several clinically important drugs whose therapeutic efficacy is due in part to their ability to act upon ion channels prevalent in nearly all biological systems. In studying eukaryotic and prokaryotic organisms in vitro, we show that ketamine short-circuits the growth and spatial expansion of three microorganisms, Stachybotrys chartarum, Staphylococcus epidermidis and Borrelia burgdorferi, at doses efficient at reducing depression-like behaviors in mouse models of clinical depression. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…alpha diversity: no significant difference ( Getachew et al, 2018 ) in vitro (ketamine and propofol mix) antimicrobial activity against E.coli, P.aeruginosa and C.albicans. S.aureus not inhibited ( Begec et al, 2013 ) in vitro dose dependent antimicrobial activity against: S.aureus, S.pyogenes, S.epidermidis, E.faecalis, P.aeruginosa and E.coli S.aureus and S.pyogenes most sensitive ( Gocmen et al, 2008 ) in vitro antimicrobial activity against Stachybotrys chartarum, Staphylococcus epidermidis and Borrelia burgdorferi ( Torres et al, 2018 ) MDMA male rats, MDMA 20 mg/kg, single dose, subcutaneous inhibits serotonin (SERT), norepinephrine (NET), and dopamine transporters (DAT) increase in cecal Proteus mirabilis vs placebo, antibiotics reduced MDMA-induced hyperthermia ( Ridge et al, 2019 ) SSRI's male mice, escitalopram 10 mg/kg, oral gavage, daily stress (CUMS) inhibits SERT responder group: increase in Prevotellaceae UCG-003, and decrease in Ruminococcaceae and Lactobacillaceae vs non-responder group. escitalopram increased alpha-diversity ( Duan et al, 2021 ) male mice, amitriptyline (25 mg/kg/d) or fluoxetine (12 mg/kg/d) for 6 weeks, oral gavage, daily stress (CUMS) increase in Bacteroidetes and decrease in Firmicutes, increase in Porphyromonadaceae increase in Bacteroidaceae associated with Ami, not Flu increase in Parabacteroides, Butyricimonas , and Alistipes in Ami and Flu alpha diversity increased in Ami and Flu ( Zhang et al, 2021 ) male rats, 28 days fluoxetine 10 mg/kg/day, escitalopram 5 mg/kg/day, in drinking water fluoxetine inhibited growth of cecal Succinivibrio and Prevotella SSRIs: increase ileal but not colonic permeability in vitro: escitalopram antimicrobial activity against E.coli , but not L.rhamnosus.…”
Section: Communication Channels: Microbiota-gut-brain (Mgb) Axismentioning
confidence: 99%
“…alpha diversity: no significant difference ( Getachew et al, 2018 ) in vitro (ketamine and propofol mix) antimicrobial activity against E.coli, P.aeruginosa and C.albicans. S.aureus not inhibited ( Begec et al, 2013 ) in vitro dose dependent antimicrobial activity against: S.aureus, S.pyogenes, S.epidermidis, E.faecalis, P.aeruginosa and E.coli S.aureus and S.pyogenes most sensitive ( Gocmen et al, 2008 ) in vitro antimicrobial activity against Stachybotrys chartarum, Staphylococcus epidermidis and Borrelia burgdorferi ( Torres et al, 2018 ) MDMA male rats, MDMA 20 mg/kg, single dose, subcutaneous inhibits serotonin (SERT), norepinephrine (NET), and dopamine transporters (DAT) increase in cecal Proteus mirabilis vs placebo, antibiotics reduced MDMA-induced hyperthermia ( Ridge et al, 2019 ) SSRI's male mice, escitalopram 10 mg/kg, oral gavage, daily stress (CUMS) inhibits SERT responder group: increase in Prevotellaceae UCG-003, and decrease in Ruminococcaceae and Lactobacillaceae vs non-responder group. escitalopram increased alpha-diversity ( Duan et al, 2021 ) male mice, amitriptyline (25 mg/kg/d) or fluoxetine (12 mg/kg/d) for 6 weeks, oral gavage, daily stress (CUMS) increase in Bacteroidetes and decrease in Firmicutes, increase in Porphyromonadaceae increase in Bacteroidaceae associated with Ami, not Flu increase in Parabacteroides, Butyricimonas , and Alistipes in Ami and Flu alpha diversity increased in Ami and Flu ( Zhang et al, 2021 ) male rats, 28 days fluoxetine 10 mg/kg/day, escitalopram 5 mg/kg/day, in drinking water fluoxetine inhibited growth of cecal Succinivibrio and Prevotella SSRIs: increase ileal but not colonic permeability in vitro: escitalopram antimicrobial activity against E.coli , but not L.rhamnosus.…”
Section: Communication Channels: Microbiota-gut-brain (Mgb) Axismentioning
confidence: 99%
“…A potential source for these molecules is the trillions of microbes that reside within the human gastrointestinal tract. Indeed, microbes can produce 5-HT, DA, glutamate, γ-aminobutyric acid (GABA) and other chemical ligands used by neurons to run a functioning brain [22][23][24]. As these ligands and their metabolic by-products can be absorbed into the bloodstream and delivered to the brain across circumventricular areas (e.g., organum vasculosum of the lamina terminalis), cranial nerves (e.g., vagus nerve X), and/or meninges (e.g., dural venous sinuses), it is conceivable that additional 5-HT or DA levels may disrupt the balance of excitatory and inhibitory mechanisms that determine the strength of synaptic transmission [25,26].…”
Section: Box 2: Open Questionsmentioning
confidence: 99%
“…In a more recent study on radish seeds treated with sub-anesthetic doses of ketamine, the authors observed the antibacterial effect on S. epidermidis and Borrelia burgdorferi . They concluded that the possible mechanism behind this effect could remain in l -glutamate signaling networks and NMDAR ion channels of bacteria (Torres et al, 2018 ).…”
Section: Antibacterial Effect Of Ketaminementioning
confidence: 99%